Aflatoxin contamination of animal feeds and its predictors among dairy farms in Northwest Ethiopia: One Health approach implications - Tadele, Fitalew; Demissie, Biruk; Amsalu, Alebachew; Demelash, Habtamu; Mengist, Zelalem; Ambelu, Argaw; Yenew, Chalachew (Frontiers in Veterinary Science, 2023)
Background: In the dairy farming, animal feeds are the first line of food safety. Animal feeds can become contaminated and spoiled on farms or in storage facilities with the diverse microorganisms that are naturally present around or on various animal feeds. The study aimed to assess the level of aflatoxin and predictors in animal feeds among dairy farms in South Gondar Zone, Ethiopia. Methods: A total of 100 samples of each animal feed ingredient (aettela, hay, commercial concentrates, and cut carry pasture) obtained. The total of 400 animal feed ingredient samples were tested separately among 100 randomly chosen dairy farmers for aflatoxins analysis. Simultaneously, swabs from cow udders and water samples were also collected. Through the use of a structured and pretested questionnaire, the Knowledge, and practices of animal feed administrators responsible for managing animal feed also evaluated. Descriptive statistics and logistic regression models used to identify determinants. Results: From the total animal feed analyzed, 96% were positive for aflatoxins. Finally, feed storage facility, feed storage duration, educational of animal feed administrators, mixed concentrates, and previous training were associated with an aflatoxin’s contamination level of animal feeds. Conclusions: The levels of aflatoxins contamination in animal feeds were relatively higher than the recommended limit, The finding suggests the spread of aflatoxin contamination between humans and animals. Besides, the occurrence of them in the environment results from milk can become contaminated with aflatoxins. One Health strategy should therefore receive special consideration to tackle such problems and safeguard consumer safety.